2012
DOI: 10.1088/0004-637x/760/1/66
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR LINE OBSERVATIONS OF THE CARBON-RICH CIRCUMSTELLAR ENVELOPE CIT 6 AT 7 mm WAVELENGTHS

Abstract: We present a λ7 mm spectral line survey of the carbon-rich circumstellar envelope (CSE) CIT 6 using the 45 m telescope at the Nobeyama Radio Observatory. A total of 25 spectral features belonging to five molecular species (HC 3 N, HC 5 N, HC 7 N, SiO, and CS) are detected, enabling us to investigate the chemistry of cyanopolyyne chains. The line strengths are compared with those of the proto-typical carbon-rich CSE IRC+10216. The results show that the cyanopolyyne molecules are enhanced in CIT 6, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
4
15
1
Order By: Relevance
“…Generally, HC 5 N lines are stronger than HC 7 N lines, and show less symmetric profiles. As noted in Chau et al (2012), a similar trend, namely that the profile asymmetry is less for the larger molecule, is observed when comparing the HC 3 N and HC 5 N transitions at a higher frequency regime.…”
Section: Observational Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Generally, HC 5 N lines are stronger than HC 7 N lines, and show less symmetric profiles. As noted in Chau et al (2012), a similar trend, namely that the profile asymmetry is less for the larger molecule, is observed when comparing the HC 3 N and HC 5 N transitions at a higher frequency regime.…”
Section: Observational Resultssupporting
confidence: 81%
“…In particular, the survey of Gong et al (2015), which covered the 17.8 -26.3 GHz frequency range, detected a total of 78 transitions from known molecular species, amongst which 23 were detected for the first time outside the solar system. Our research group has been engaged in a long-term project to perform systematic spectral line surveys in a large sample of evolved stars with comprehensive wavelength coverage (He et al 2008;Zhang et al 2008Zhang et al , 2009aChau et al 2012;Zhang et al 2013). In the present paper, we investigate the 20-25 GHz spectra of a sample consisting of C-rich CSEs including IRC+10216, CRL 2688, CRL 618, and NGC 7027. Displayed in Table 1 are the physical properties of the scientific objects consolidated from a series of literature searches.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the previous spherical shell model (Claussen et al 2011) and incomplete shell model (Chau et al 2012) required the use of individual shell parameters without providing physical understanding for their variations. Moreover, the binary model reveals that the knotty structures result from the overlapping between a spiral-shell-shaped pattern due to the orbital motion of the mass-losing star and a more flattened spiral pattern onto the orbital plane due to the companion's motion.…”
Section: Discussionmentioning
confidence: 99%
“…Claussen et al (2011) remarked on the existence of the asymmetric features such as the spiral shape (relatively well traced in the velocity channel of −7.4 km s −1 ), stronger emission observed in the redshifted side, and lack of emission in the west and northwest near the central channels. Chau et al (2012) showed that the optical depth effect cannot reproduce the asymmetric line profile of CIT 6 for a physical structure assumed to be spherically symmetric. Their three-dimensional morphokinematic model instead suggested several incomplete shells for the structure of CIT 6.…”
Section: Known Facts On Cit 6 As Model Constraintsmentioning
confidence: 99%
“…It is likely induced by a central binary star (Kim et al 2013), and extends over 20 . In fact, the molecular content of the RW LMi envelope suggests that this object is more evolved than IRC+10216 (Chau et al 2012). The interferometric observations of Lindqvist et al (2000) reveal a CN ring with a radius of 2675-3340 AU.…”
Section: Source Samplementioning
confidence: 97%